Home environment factors associated with early childhood development in rural areas of Bangladesh: evidence from a national survey - Rahman, Farzana; Tuli, Samiha Nahar; Mondal, Prasenjit; Sultana, Shakina; Hossain, Asmita; Kundu, Satyajit; Clara, Afrin Ahmed; Hossain, Ahmed (Frontiers in Public Health, 2023)
Background: Knowing the relationship between the factors related to home environment and early childhood development (ECD) in Bangladeshi children aged 3 to 4 years would help to find out appropriate interventions for the children with lower ECD outcomes. Therefore, we aimed to understand the relationship between the home environment factors and ECD in rural Bangladeshi children aged 3 to 4 years. Methods: We used data from the Multiple Indicator Cluster Survey (MICS) 2019, and included 7,326 rural children aged 3 to 4 years. The ECD index (ECDI) included four domains: literacy-numeracy, learning, physical and socio-emotional development. If a child met at least three of these four domains, the child was indicated as developmentally ‘on-track’. Results: The findings show that 27.4% of rural children missed to reach developmentally on-track while 72.2% of children didn’t attain the literacy-numeracy domain of ECD. The home environment factors including parental participation in children's activities, was found to be associated with ECD. For instance, reading books to child had 26% (aOR= 1.26, 95% CI=1.08-1.48), and telling stories to child had 29% (aOR= 1.29, 95% CI= 1.09-1.53) more developmentally on-track in overall ECDI. Similar associations between home environment factors and specific ECD domains were also obtained. We also identified that children aged 4 years, girls, and children of mothers with higher socio-economic status (SES) were higher developmentally on-track than their counterparts. Conclusions: Home environment factors like reading books and telling stories to children were found to be significantly associated with ECD in rural areas of Bangladesh. Our study's findings would assist in implementing the essential public health intervention to enhance the ECD program especially in the rural Bangladeshi context.